Strengthening Cooperation Between Subject Teachers And Guidance And Counseling Teachers In The Framework Of Preserving Academic Culture In Schools - Fakhri Yacob Fakhri (Bansigom Na Publisher, 2025)
This article explores the essential role of cooperation between subject teachers and guidance and counseling teachers in maintaining and enhancing the academic culture within schools. The preservation of academic culture is vital for fostering a conducive learning environment that promotes students' intellectual growth, emotional well-being, and social development. The study employs a qualitative approach, utilizing interviews and focus group discussions with educators from various schools to identify strategies and best practices for strengthening collaboration between these two essential roles. Findings reveal that effective communication, mutual respect, and shared goals are critical components of successful partnerships. Additionally, the integration of guidance and counseling into subject teaching not only supports students' academic performance but also addresses their psychosocial needs, contributing to a holistic educational experience. The article concludes by recommending practical measures to enhance collaboration, including regular joint training sessions, development of integrated curricula, and ongoing evaluation of cooperative efforts. By fostering a collaborative framework, schools can significantly improve their academic culture, ultimately leading to better educational outcomes for students.